Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Guru - Gantang Suwarga; Ai Revi Resmiati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of education and training as well as compensation on teacher performance through teacher loyalty. This study uses a quantitative method where research is presented through numbers. The total population in this study is 171 educators. The sampling technique is probability sampling, which means a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. The number of samples is carried out by means of statistical calculations, namely using the slovin formula. Data collection used the method of observation, questionnaires and documentation, which were processed using the Rxy test and analyzed through the t test and KD test. Based on Rxy, it can be seen that between variables X and Y there is a very high correlation taking into account the magnitude of Rxy (0.74), located between 0.71 – 0.90. And based on the t test, it was found that the tcount was greater than 11.851 while the ttable was 1.657 with a significant level of 0.05 Df 118. So there was a significant or positive effect. This means that the Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted, because t count is greater than t table. And based on the KD test, it found a value of 54.76%, meaning that there was a contribution of Variables X1, X2 and Variable Y while 45.24% was influenced by other factors.